Sexual and reproductive health challenges among adolescents and young people with spina bifida and hydrocephalus disability in Uganda: A qualitative study - Denis Ndekezi; Andrew Sentoogo Ssemata; Ambrose Ganshanga; Ruth Nalugya (PLoS ONE, 2025)
Introduction Globally, 180 million young people aged 10–24 live with a physical or mental health disability. Their rights to sexual and reproductive health have been denied often overshadowed by the societal negative knowledge, beliefs, and attitudes. This study sough to explore sexual and reproductive health challenges among adolescents and young people with spina bifida and hydrocephalus disability in Uganda. Methods This was an exploratory community based cross-sectional qualitative study among adolescents in Uganda. We conducted 60 semi structured interviews, 30 with Adolescents and young people with spina bifida and hydrocephalus and 30 with caregivers between March 2021 and February 2022 to explore their sexual and reproductive health challenges. Through thematic analysis, we identified common themes across the interviews regarding their challenges. Results Participants reported a number of sexual and reproductive health challenges including sexual violence and abuse, incontinence and stigma, Inability to feel sexually empowered, other adolescents are coerced to take birth control methods without their informed decision. Negative Socio-cultural beliefs, lack of and inaccessible sexual reproductive health information and poor menstrual health management. Conclusion Adolescents and young people with spina bifida experience a number of sexual and reproductive challenges that are not given attention and often overshadowed by the negative knowledge, beliefs, attitudes, and practices within the society. Therefore, there is need to develop and implement programs and awareness campaigns aimed for the empowerment of individuals with SB to seek knowledge and skill building regarding sexual and reproductive health.